Teacher Techniques in Encouraging Students to Speak English Through Flipgrid: A Systematic Literature Review - Lutpiyah Lutpiyah; Salsabila Fitriyani; Muhammad Hanafi; Naf’an Tarihoran (PT. Intelek Cendikiawan Nusantara, 2025)
This study analyzes how teaching tactics such as Flipgrid can effectively motivate students to speak English in EFL classrooms, a skill that remains challenging due to nervousness, limited practice time, and traditional, instructor-centered instruction. The objective of this research is to integrate previous empirical studies to understand how Flipgrid is used, how it enhances speaking performance, and the pedagogical strategies teachers employ when incorporating the platform. This study used a Systematic Literature Review (SLR) method following PRISMA criteria, reviewing publications from 2020 to 2025 across databases such as PubMed, ScienceDirect, ERIC, Mendeley, and ResearchGate. A total of 224 papers were identified, and after screening and eligibility verification, nine studies were selected for in-depth analysis. The results demonstrate that Flipgrid helps students build their speaking skills by offering opportunities for repeated practice, lowering speaking anxiety, enhancing fluency, pronunciation, and encouraging peer interaction. To maximize student involvement, teachers frequently use strategies including task-based speaking, structured video prompts, peer review, and reflective practice. The study finds that Flipgrid is a powerful pedagogical tool for developing EFL speaking skills, with implications for designing more dynamic, technology-integrated language learning environments.